An Analysis of Canadian Institute for Health Research Funding for Research on Autism Spectrum Disorder. (10th February 2016) - Deonandan, R.; Liu, E. Y.; Kolisnyk, B.; Konkle, A. T. M.
Abstract : We examined patterns of Canadian Institute for Health Research (CIHR) funding on autism spectrum disorder (ASD) research. From 1999 to 2013, CIHR funded 190 ASD grants worth $48 million. Biomedical research received 43% of grants (46% of dollars), clinical research 27% (41%), health services 10% (7%), and population health research 8% (3%). The greatest number of grants was given in 2009, but 2003 saw the greatest amount. Funding is clustered in a handful of provinces and institutions, favouring biomedical research and disfavouring behavioural interventions, adaptation, and institutional response. Preference for biomedical research may be due to the detriment of clinical research.